Asociación entre la ferropenia y las escalas funcionales New york Heart Association (NYHA) y la fracción de eyección del ventrículo izquierdo (FEVI) en los pacientes con diagnostico con insuficiencia cardiaca descompensada (2024)
Objective: To characterize iron deficiency patients diagnosed with heart failure and to analyze probable associations between the New York Heart Association (NYHA) scales and the left ventricular ejection fraction (LVEF) in a third level hospital in Bogotá Dc. Methods: A descriptive cross-sectional study was carried out that reviewed retrospective information obtained from the medical records of patients over 18 years of age hospitalized in the Central East Integrated Health Services Subred, Bogotá, Colombia. Results: Of a total of 139 hospitalized patients in the study period, a prevalence of heart failure with reduced LVEF was obtained 45.3%, mean age 53 years, 67.6% men, comorbidities such as atrial fibrillation 23.2%, coronary disease 59%. and dyslipidemia 27.9%, 57.2% patients had iron deficiency. They were found as factors associated with NYHA III and IV; male sex (OR: 2.8; 95% CI: 1.17;6.97), chronic obstructive pulmonary disease (OR: 2.7; 95% CI: 1.03;7.23), iron deficiency ( OR: 1.92; 95% CI: 1.13;3.25). Conclusions: Most of the patients were classified with reduced and slightly reduced heart failure 45%, with anemia and iron deficiency. It was observed that male sex, chronic obstructive pulmonary disease, diagnosis of iron deficiency, total iron >40 mcg/dL, hemoglobin <13g, age younger than 65 years, and a history of coronary disease can be associated with reduced ejection fraction and NYHA classification stages III and IV.